SQ4R (Survey, Question, Read, Recite, Review, and Reflect) and Students’ Reading Attitude Toward Their Reading Comprehension - Jelita Jelita (Pendidikan Bahasa Inggris STKIP Nurul Huda, 2018)
The aims of the study were to find out whether or not (1) there is any significant difference in reading comprehension between the students who had positive and negative attitude in experimental class, (2) there is any significant difference in reading comprehension between the students who had positive and negative attitude in control class,(3) there is any significant difference in reading comprehension among the students who had positive attitude in control and experimental class,(4) there is any significant difference in reading comprehension between the students who had negative attitude in control and experimental class, (5) there is any interaction effect between SQ4R strategy and reading attitude in increasing reading comprehension. The population of this study was all the eleventh class students consisted of 144 students of SMA N I Buay Madang OKU Timur. The 72 sample students were taken by using stratified random sampling. In carrying out the research, the researcher used the true experimental factorial design. The writer distributed the pretest, posttest, and questionnaire on students' reading attitude (positive and negative) in collecting the data. In analyzing the data, t-test and two-way ANOVA were used. There is any significant difference between posttest and pretest in Experimental class, there is any significant difference between posttest and pretest in control class, there is significantly different on Positive Attitude students in experimental class and Positive Attitude students in control class, there is significant difference between negative Attitude students in experimental class and negative Attitude students in control class. The last, there was no any significant interaction between the students' reading attitude and strategies used.